Etika Mahasiswa dalam Pergaulan Sehari-hari: Studi terhadap Batasan Interaksi dalam Fiqih - Syifa Al Ghefira; Zakiah Zahran Febridirani; Bagus Nova Kamajaya; Suci Kurnia; Imam Tauhid (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
The social interactions of university students in the modern era show significant shifts in ethical values, both in direct communication and through digital media. These changes raise questions about the relevance of fiqh as a guiding framework for regulating student interactions. This study examines the concept of social interaction in Islam, ethical principles for students, the boundaries of interaction between men and women through the concepts of ikhtilāṭ and khalwah, as well as communication ethics in both real and digital settings. Using a literature review method and a descriptive-analytical approach to classical and contemporary sources, the study finds that Islam provides ethical guidelines emphasizing dignity, proper conduct, moral responsibility, and the prevention of social deviation. For students, these principles guide polite, professional, and proportional behavior in all forms of interaction. Fiqh remains relevant as an ethical reference for social interactions, adaptable to modern developments without abandoning its core moral values.